The Presence of Other TB Cases in the Family as a Substantial Factor Influencing the Level of Knowledge and Perception of TB patients - Yelvi Levani; Ricky Indra Alfaray; Rahmat Sayyid Zharfan; Astri Dewayani; Kartika Afrida Fauzia; Batsaikhan Saruuljavkhlan; Ayu Lidya Paramita; Maya Rahmayanti; Nur Mujaddidah Mochtar; Kamal Musthofa; Dede Nasrullah; Mohammad Subkhan (Faculty of Medicine, Universitas Airlangga, Surabaya, Indonesia, 2021)
Introduction: Indonesia is still among the top three contributors to the number of Tuberculosis (TB) patients in the world in 2017. The awareness about TB can be affected by the presence of other TB patients in the family. Perception and good knowledge in TB patients can increase obedient in treatment. This study aims to relate to the presence of other TB patients in the family environment with knowledge of TB patients.Methods: This study used cross-sectional design. Research respondents have taken using the consecutive sampling technique. Respondents were TB patients on category one anti-tuberculosis treatment at Siti Khadijah Sepanjang Hospital and several primary health centers in Sidoarjo region during February-March 2019. This study used a questionnaire which included sociodemographic, level of knowledge, and perception about TB.Results: The number of respondents in this study was 50 people aged 22-67 years old. The level of knowledge of the respondents was mostly good (82%) as well as perceptions regarding TB (78%). Of the 50 patients, 17 patients (34%) claimed some families also suffered from TB. The comparison between group with other TB patient and group without other TB patients in the family showed significantly different result in the level of knowledge (p=0,000) and perception (p=0,000). The presence of other TB cases in family increased level of knowledge and perception regarding TB significantly.Conclusion: The presence of other TB patients in the family environment can increase awareness so that it can increase the interest of TB patients to find information about TB.